2010
DOI: 10.1002/jls.20136
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit mergers: Assessing the motivations and means

Abstract: As nonprofit organizations seek to remain viable in an increasingly competitive environment, merger is an attractive (albeit complicated) option. This case study of the largest nonprofit association merger in U.S. history, involving three bowling associations, demonstrates the critical role of leadership in consummating a merger. The case illustrates a number of factors necessary to merger success: existence of a catalyst leader and a nucleus of like-minded individuals who can serve as the impetus for change, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Thus allowing time to discuss potential conflicts of service must be a revealed to assure appropriate mission connectivity and what would strengthen the organizational mission, not detract from it. This finding is also consistent with previous research (Pietriburgo & Wernet, 2010). Cultural attitudes and personality can also be strong and significant waves that ripple through the board and the organization.…”
Section: Pre-strategy Assessmentsupporting
confidence: 93%
“…Thus allowing time to discuss potential conflicts of service must be a revealed to assure appropriate mission connectivity and what would strengthen the organizational mission, not detract from it. This finding is also consistent with previous research (Pietriburgo & Wernet, 2010). Cultural attitudes and personality can also be strong and significant waves that ripple through the board and the organization.…”
Section: Pre-strategy Assessmentsupporting
confidence: 93%
“…Mergers among nonprofit organizations (including trade unions, trade and professional associations) are quite common but difficult to manage successfully (Aldrich, Zimmer, and Udo, ; Pietroburgo, and Wernet, , ; Stevens, ; Hoffman, Kahmann, and Waddington, ). The motivation for merger often lies in shifting patterns of client needs and the inherent financial uncertainty of a nonprofit organization (Pietroburgo and Wernet, ). In accounting, in particular, the market is dynamic resulting in difficulties for professional associations to define and retain control over the cognitive domain within which their members would practice (Richardson, ).…”
Section: Prior Literature and Research Questionsmentioning
confidence: 99%
“…Some research acknowledges that mergers may provide an opportunity to scale up similar services or add new programs to an existing portfolio; for example, Wernet and Jones () indicated that mergers can be horizontal, in that they involve two organizations providing similar services; vertical, in that they involve organizations working to provide different services within the same system; or conglomerate in that organizations operate in different fields altogether. Another, lesser‐known merger catalyst is “precursor partnering.” Pietroburgo and Wernet () suggest that a previous relationship with another agency, such as sharing space or administrative activities, could help the entities become familiar with each other and lead to mergers. In their study of the U.S.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another, lesser-known merger catalyst is "precursor partnering." Pietroburgo and Wernet (2010) suggest that a previous relationship with another agency, such as sharing space or administrative activities, could help the entities become familiar with each other and lead to mergers. In their study of the U.S.…”
Section: Nonprofit Mergers: Definitions and Catalystsmentioning
confidence: 99%